2022
DOI: 10.1094/phytofr-08-21-0051-r
|View full text |Cite
|
Sign up to set email alerts
|

The Pursuit in Nepal of Native Trichoderma spp. for Plant Disease Biocontrol

Abstract: The characteristics of 41 native Trichoderma isolates collected from diverse microclimatic domains in Nepal and two Ohio isolates, and their efficacy in biocontrol of plant diseases were assessed. Species assignment was based on a maximum likelihood phylogenetic analysis constructed on a concatenated dataset using the internal transcribed spacer region (ITS), translocation elongation factor (tef1) and RNA polymerase II subunit (rpb2). Most of the Nepal isolates (n=37) were assigned to the Viride clade and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Their results showed that the cell wall degrading enzyme, endoglucanase, contributed to the antagonistic activity of T. citrinoviride toward pathogens. Moreover, a study by Khadka et al [75] revealed reduced mycelial growth of Rhizoctonia solani by T. ghanense.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that the cell wall degrading enzyme, endoglucanase, contributed to the antagonistic activity of T. citrinoviride toward pathogens. Moreover, a study by Khadka et al [75] revealed reduced mycelial growth of Rhizoctonia solani by T. ghanense.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we report the evaluation of novel Trichoderma isolates collected from different agroecological regions of Nepal for their ability to proliferate under osmotic stress and then to mitigate stress responses in tomato genotypes during and after exposure to water deficit conditions. We had a unique opportunity to test isolates from highly diverse ecological niches ranging in mean annual precipitation from <200 to 5,000 mm, in elevation above sea level from 58 to 8,848 m, and temperature extremes from –12°C to 43.3°C ( Karki et al, 2016 ; Khadka et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Forty-one different Trichoderma isolates collected from diverse agroecological regions of Nepal (designated as NT1-NT39, NT42, NT43) and two Trichoderma isolates from Ohio (OT41, OT42) were selected for this study. Molecular and morphological characterization of all isolates used in this study is presented in Khadka et al (2022) . Nepalese Trichoderma isolates were recovered from diverse agricultural soils found at environmentally diverse sites (arid, saline, alpine regions), representing potential reservoirs of microorganisms with traits that may benefit plant hosts when grown under differing environmental conditions ( Supplementary Figure 1 and Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%